Deglaciation dynamics of the Fennoscandian Ice Sheet in the Kattegat, the gateway between the North Sea and the Baltic Sea Basin. (2nd December 2020) - Hyttinen, Outi; Quintana Krupinski, Nadina; Bennike, Ole; Wacker, Lukas; Filipsson, Helena L.; Obrochta, Stephen; Jensen, Jørn B.; Lougheed, Bryan; Ryabchuk, Daria; Passchier, Sandra; Snowball, Ian; Herrero‐Bervera, Emilio; et al.
Abstract : This paper presents an age–depth model based on an ultra‐high‐resolution, 80‐m‐thick sedimentary succession from a marine continental shelf basin, the Kattegat. This is an area of dynamic deglaciation of the Fennoscandian Ice Sheet during the Late Pleistocene. The Kattegat is also a transitional area between the saline North Sea and the brackish Baltic Sea. As such, it records general development of currents and exchange between these two systems. Data for the succession were provided through the Integrated Ocean Drilling Program Site M0060. The site indicates onset of deglaciation at c . 18 ka BP and relatively continuous sedimentation until 13 ka BP. At this point, sediments record a hiatus until c . 9–7 ka BP. The uppermost sedimentary unit contains redeposited material, but it is estimated to represent only the last c . 9–7 ka BP. The age–depth model is based on 17 select, radiocarbon‐dated samples and is integrated with a set of physical and chemical proxies. The integrated records provide novel constraints on the timing of major palaeoenvironmental changes, such as the transition from glaciomarine proximal to glaciomarine distal and marine conditions, and their connections to known major events and processes in the region and the North Atlantic. Depositional evidence specifically documents connections between the Fennoscandian Ice Sheet behaviour and atmospheric and oceanic warming. Glacial retreat may have also depended on topographic factors such as changes in basin width and depth, linked to relative sea level changes and land uplift. The results indicate an early response of the Fennoscandian Ice Sheet to changing climate, and the ice sheet's possible influence on oceanic circulation during the Late Pleistocene deglaciation.